Birth injury as a causative factor of syringomyelia with Chiari type I deformity. Issue 3 (March 1994) - Hida, K; Iwasaki, Y; Imamura, H; Abe, H
Abstract : The epidemiology of syringomyelia with Chiari type I deformity was investigated with particular reference to perinatal problems. All subjects in our study were born by vaginal delivery and had a high incidence of perinatal accidents (abnormal presentations, birth injuries, and neonatal asphyxia). This study suggests that these may be strong causative factors for syringomyelia associated with Chiari type I deformity.